2016
DOI: 10.11138/jts/2016.4.4.214
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance with new oral anticoagulants after major orthopaedic surgery: rivaroxaban and dabigatran compared with subcutaneous injection of fondaparinux

Abstract: Purpose: the main purpose of our study was to compare patient compliance with the orally administered new oral anticoagulants (noCs) dabigatran and rivaroxaban compared with subcutaneously injected fondaparinux after major orthopaedic surgery, and to assess patient preference for the oral vs subcutaneous administration route. Methods: prophylactic antithrombotic drug therapy with dabigatran (group D; GD, n=32 patients), rivaroxaban (group R; GR, n=38 patients) or fondaparinux (group F; GF, n=30 patients), to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Many factors contribute to patient adherence to medications including convenience, cost, dosing regimen, side effects, and patient education. In comparison to traditional VTE prophylaxis regimens that may require frequent injections and laboratory monitoring, aspirin is administered orally and may be preferred by some patients [15] . The cost of aspirin is also less than other traditional VTE prophylaxis agents such as warfarin, dabigatran, and rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors contribute to patient adherence to medications including convenience, cost, dosing regimen, side effects, and patient education. In comparison to traditional VTE prophylaxis regimens that may require frequent injections and laboratory monitoring, aspirin is administered orally and may be preferred by some patients [15] . The cost of aspirin is also less than other traditional VTE prophylaxis agents such as warfarin, dabigatran, and rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…A third and fourth dose per day decreased adherence further to 65% and 51%, respectively. Other studies reported greater than 90% adherence to VTE prophylaxis after a THA, using a once-daily dosing regimen [15] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…5 A second study (n = 130) reported very high adherence rates, with 97% (n = 38) adherent to rivaroxaban, 100% (n = 32) to dabigatran (oral) and 100% (n = 30) to fondaparinux (injection). 11 The lack of consistent results across each of the studies above and our study may be due to the heterogeneity of adherence questionnaires used, heterogeneity in indication for surgery and demographics across study populations (trauma and arthroplasty) as well as suboptimal power due to the relatively small sample sizes. Further evidence is required to investigate the hypothesis that adherence to enoxaparin is lower than aspirin after hospital discharge following THA or TKA, given enoxaparin's greater effectiveness in preventing symptomatic 90-day VTE.…”
Section: Discussionmentioning
confidence: 72%
“…There have been two studies comparing adherence rates for aspirin to LMWH following orthopaedic trauma 9,10 and two studies comparing adherence for DOACs (oral prophylaxis) to LMWH following THA and TKA. 5,11 Like this study, each hypothesised greater adherence with oral compared to injectable medications, due to their greater ease of administration. The first study in orthopaedic trauma patients (n = 150) reported non-adherence of 29% with aspirin (81 mg BD orally) and 41% with LMWH (30 mg BD, subcutaneously) while the second (n = 61) reported non-adherence of 37% with aspirin (75 mg, frequency not provided) and 19% with LMWH (dose and frequency not provided).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation